In vivo evaluation of DSAEK interface with scanning-laser confocal microscopy - Ferrari Giulio (BMC Ophthalmology, 2012)
Abstract Background Descemet Stripping Automated Endothelial Keratoplasty (DSAEK) allows selective replacement of the endothelium. Post-operative haze and particles can affect the interface quality and, ultimately, visual outcome. In this study, we evaluated DSAEK interface with in vivo laser confocal microscopy (LCM) in order to: (i) correlate interface status with best corrected visual acuity, and (ii) with time from surgery; (iii) correlate interface particle number with best corrected visual acuity. Host-donor interface was imaged and graded using a published reflectivity scale. Particles at the interface were counted. Methods 18 eyes of 16 patients (6 males and 10 females); mean age: 74 ± 8.3 years which underwent DSAEK were examined by means of in vivo laser confocal microscopy between 1 and 24 months after surgery. Host-donor interface was imaged and graded using a published reflectivity scale. Particles present at the interface were counted. Results Interface reflectivity was 2.17 ± 1.2 and significantly correlated with visual acuity (Spearman correlation coefficient −0.83; P < 0.001), and with time after surgery (Spearman correlation coefficient −0.87; P < 0.001). Visual acuity was 0.67 ± 0.27. The number of particles was 205 ± 117.8; no correlation was found between this number and visual acuity (Spearman correlation coefficient −0.41; P = 0.15). Conclusion DSAEK interface imaged with LCM is helpful in diagnosing poor host-donor interface quality in DSAEK surgery. A good quality interface is related to a better visual acuity. Moreover, the quality of the interface appears to improve as time passes from the surgery. Interface quality is related with visual acuity and improves with time from surgery. LCM should be considered as an added tool in post-DSAEK follow-up of patients. Finally, our study shows that the presence of particles does not influence visual outcome.